Supercritical carbon dioxide extraction of Ganoderma lucidum spore lipids. (July 2016) - Li, Jinwei; Zhang, Xinxin; Liu, Yuanfa
Abstract: In this paper extraction of G. lucidum spore lipids (GSL) by supercritical fluid extraction technology (SFE) was optimised and compared with soxhlet and sonication extraction. Response surface methodology was employed to study the effects of extraction pressure, time and temperature on the lipids yield. Under the optimal SFE conditions of pressure of 35 MPa, time of 3 h and temperature of 48 °C, the lipids yield could reach 29.50%, which was significantly greater than that of sonification method (23.74%) and was no significant difference compared to that of soxhlet extraction (30.02%). Fatty acid analysis showed that oleic acid, palmitic acid and linoleic acid were the main fatty acids of GSL extracted by three methods, which accounted for about 88% of total fatty acids. The total sterols content determined by GC/MS demonstrated that ergosta-7, 22-dien-3β-ol and ergosterol were the major sterol in all of the lipids extracted by SFE, Soxhlet and sonication, which represented about 80% of total sterols. Ergost-7en-3-ol ranged from 0.65 to 0.81 mg/g accounted for 21%. Ergosta-7, 22- diene-3β-5α-6β-triol ranged from 0.01 to 0.02 mg/g. The sterols content of GSL obtained by SFE with 20% ethanol as entrainer reached 3.72 mg/g, which was significantly greater than the other both methods. Highlights: The effects of SFE condition on GSL yield was investigated and optimized by RSM. Oleic acid, palmitic acid and linoleic acid were the main fatty acids of GLP extracted by three methods. The sterols of GSL by SFE was significantly greater than those of sonification and soxhlet methods.